Emergency Aid as a Palliative Measure against Social Inequalities in Brazil (Emancipação, 2022)
Emergency Aid was constituted as a social protection measure structured in the context of the COVID-19 pandemic, in order to reinforcecharacteristics linked to the form of care and understanding of poverty in the national territory. The research carried out aimed to demonstrate the structuring of Emergency Aid as a measure adopted by the State, in order to highlight its palliative character in the face of social inequalities in Brazil. The article proposes to problematize how the AE perpetuates the reproduction of social protection measures that do not affect the resolution of the causes of poverty. The methodology is supported by a qualitative approach, with an exploratory focus, using bibliographic and documentary research. The results show that poverty is perceived by the State as income discrepancy between subjects, which mischaracterizes its multidimensional aspects. The initiatives adopted are focused and palliative actions with short-term applicability, since, immediately, they show little effectiveness in meeting the demands of the population.
Keywords: Pandemic. Poverty. Social Protection.